Mesenteric Cyst Lymphangiomas in 6 years Old Boy (A Case Report) (Sirte Journal of Medical Sciences, 2022)
mesenteric cyst lymphangioma is a rare benign intra-abdominal tumour, It is located in the mesentery of the gastrointestinal tract and may extend from the base of the mesentery into the retroperitoneum. chylous ascites is an uncommon form of ascites due to leakage of lipid-rich lymph into the peritoneal cavity, it is diagnosed by the presence of milky-appearing ascites fluid and white triglyceride content >200mg/dl. We report 6-year-old boy presented progressive Vega abdominal pain over one month associated lately with abdominal distention and vomiting, abdominal ultrasound and NON-CONTRAST computed tomography (CT) revealed a large cystic abdominal lesion demonstrating multiple septations involving the retroperitoneal region. The intra-operative finding was a large yellowish septate mesenteric cyst arising from both mesenteric borders of jejunal loop extending retroperitoneal with white mesentery and multiple reactionary lymph node and chylous acites.